Alterações fisiopatológicas ao esforço em pacientes portadores da combinação fibrose e enfisema pulmonar - Costa, Camila Melo de Oliveira [UNIFESP] (2018)
Introduction: Exercise impairment (EI) is a common feature in patients with combined pulmonary fibrosis and emphysema (CPFE). Since the prevalence of pulmonary hypertension (HP) in this population is high, the hypothesis of this study is that, in addition to ventilatory and gas exchange abnormalities, cardiocirculatory alterations also contribute to the limitation of these patients. Objectives: i) to evaluate the physiopathological mechanisms of exercise limitation in patients with CPFE; ii) to evaluate the factors associated with cardiocirculatory limitation iii) to evaluate the response to short-acting bronchodilator on constant work-rate exercise test. Methods: Prospective, unicentric, descriptive study. The response to BD was evaluated using a double-blind, randomized, crossover design in patients with CPFE who submitted incremental exercise test and the constant work-rate exercise test with placebo and BD. Results: 18 patients with CPFE completed the protocol (68 ± 5,4yrs, Mahler dyspnea index:10 [8 -10], 83% males, 43 pack-years [31 – 58]). The study showed that 10/18 (55.5%) patients presented cardiocirculatory alterations; 9/18 (50%) presented ventilatory alterations (1 did not present ventilatory reserve on the incremental exercise test and 8 patients presented dynamic hyperinflation on the constant work rate exercise test) and 94.4% desaturated. In 6 patients we observed cardiocirculatory and ventilatory alterations concomitantly. The cut-off points were defined through the ROC curve to identify the presence of cardiocirculatory alterations: CVF / DCO ratio ≥ 2.2 (sensitivity: 70%, specificity: 87.5%, PPV: 87.5%, NPV: 70%), while the variable of the echocardiogram that presented the greatest association was the right ventricle (RV) ≥ 20 mm (sensitivity: 80%, specificity: 87.5%, PPV: 88.8%, NPV: 77.7%). Only 2 patients had a significant response to BD on exercise. Those who did not respond also had cardiocirculatory limitation. Conclusions: In CPFE, in addition to ventilatory and gas exchange abnormalities, cardiocirculatory limitation is also present. The response to bronchodilator is uncommon.